Geochemical Rate Models : An Introduction to Geochemical Kinetics - Rimstidt, J. Donald (Cambridge : Cambridge University Press, 2013)
This well-organised, comprehensive reference and textbook describes rate models developed from fundamental kinetic theory and presents models using consistent terminology and notation. Major topics include rate equations, reactor theory, transition state theory, surface reactivity, advective and diffusive transport, aggregation kinetics, nucleation kinetics and solid-solid transformation rates. The theoretical basis and mathematical derivation of each model is presented in detail and illustrated with worked examples from real-world applications to geochemical problems. The book is also supported by online resources: self-study problems put students' new learning into practice, and spreadsheets provide the full data used in figures and examples, enabling students to manipulate the data for themselves. This is an ideal overview for graduate students, providing a solid understanding of geochemical kinetics. It will also provide researchers and professional geochemists with a valuable reference for solving scientific and engineering problems.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Geochemical modeling; Chemical kinetics